2013
DOI: 10.1021/am3027822
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Induced Ordering in Poly(3-hexylthiophene): Role of Molecular and Process Parameters on Morphology and Charge Transport

Abstract: Facile methods for controlling the microstructure of polymeric semiconductors are critical to the success of large area flexible electronics. Here we explore ultrasonic irradiation of solutions of poly(3-hexylthiophene) (P3HT) as a simple route to creating ordered molecular aggregates that result in a one to two order of magnitude improvement in field effect mobility. A detailed investigation of the ultrasound induced phenomenon, including the role of solvent, polymer regioregularity (RR) and film deposition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 41 publications
6
105
0
Order By: Relevance
“…Such a picture would be consistent with more recent work where, also, ultrasonication was exploited to process P3HT. In this study, it was shown that the μ FET of P3HT increased by one order of magnitude for material of higher molecular weight (from 1.16 × 10 −3 cm 2 V −1 s −1 to 2.73 × 10 −2 cm 2 V −1 s −1 for a molecular weight of 47.7 kDa), although no clear correlation between thin-film microstructure and macroscopic charge transport could be established [38]. …”
Section: Influence Of Molecular Conformation Order and Chain Intercomentioning
confidence: 99%
“…Such a picture would be consistent with more recent work where, also, ultrasonication was exploited to process P3HT. In this study, it was shown that the μ FET of P3HT increased by one order of magnitude for material of higher molecular weight (from 1.16 × 10 −3 cm 2 V −1 s −1 to 2.73 × 10 −2 cm 2 V −1 s −1 for a molecular weight of 47.7 kDa), although no clear correlation between thin-film microstructure and macroscopic charge transport could be established [38]. …”
Section: Influence Of Molecular Conformation Order and Chain Intercomentioning
confidence: 99%
“…7,12,[16][17] However, as polymer regioregularity (RR) and/or MW increases, it becomes difficult to completely dissolve the semiconductor in a marginal solvent even at higher temperatures; [18][19][20][21][22] and it is these high RR and MW polymers that are more desirable for opto-electronic applications because of their improved electrical properties. 20,[22][23][24] The approach using good/poor solvent mixtures requires substantial optimization to determine the appropriate mixed solvent composition for a given polymer semiconductor (i.e., different RR or MW) in order to maximize performance. In addition, the above approaches do not provide sufficient time for favorable 4 polymer chain self-assembly; solvent characteristics can quickly change fast from "good" to "poor" due to decreased temperature or changes in the ratio between solvents in a mixed solvent approach due to rapid film solidification during processing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Well-defined and reproducible nanoscale assemblies of donor-acceptor semiconducting materials are crucial for several devices in the optoelectronic applications. [1][2][3][4] From the perspective of device applications, it is highly desirable to translate the self-assembly of small molecules to processable polymers, which is a non-trivial task.…”
Section: Introductionmentioning
confidence: 99%